SISTEM INFORMASI REAL COUNT PEMILIHAN UMUM BERBASIS WEB - Ilham Wibowo; Febi Eka Febriansyah (Jurnal Pepadun, 2021)
General election is a means of implementing people's sovereignty which is carried out directly, publicly, freely, secretly, honestly and fairly in the unitary state of the Republic of Indonesia based on Pancasila and the 1945 Constitution. long. Candidate supporters have difficulty knowing the progress of the candidate's vote. The presence of technology such as Quick Count currently has important benefits in elections in every region, even at the level of the Presidential Election (Presidential Election). Many survey institutions such as LSI, LP3ES, Puskaptis, Cirus Surveyors Group, LRI and others conduct quick count surveys to find out the results of the Presidential Election. However, the results of the Quick Count that differ from several other survey institutions have triggered disputes between candidate supporters because they claim to be winners. Based on this, a Web-based General Election Real Count information system is proposed that can display the vote count results in detail at each TPS. In addition, it can be used as a comparison to the results of calculations made by the KPU.